(untitled) - Franzoi, Stephen L. (Madison, Wiscosin, 1996)
Stephen Franzoi combines an exceptional writing style, classic and current research and insightful, up-to-the-minute examples to provide students with a full understanding of social psychology. Social Psychology's exceptional writing style, combined with the use of classic and current research as well as relevant and personal examples, provide students with an extraordinary text that aids in understanding the importance of social problems.
Keywords: Social psychology